PICT: A low-cost, modular, open-source camera trap system to study plant–insect interactions - Droissart, V.; Azandi, L.; Onguene, E.R.; Savignac, M.; Smith, T.B.; Deblauwe, V. (Wiley, 2021)
Commercial camera traps (CTs) commonly used in wildlife studies have several technical limitations that restrict their scope of application. They are not easily customizable, unit prices sharply increase with image quality and importantly, they are not designed to record the activity of ectotherms such as insects. Those developed for the study of plant–insect interactions are yet to be widely adopted as they rely on expensive and heavy equipment. We developed PICT (plant–insect interactions camera trap), an inexpensive (<100 USD) do-it-yourself CT system based on a Raspberry Pi Zero computer designed to continuously film animal activity. The system is particularly well suited for the study of pollination, insect behaviour and predator–prey interactions. The focus distance can be manually adjusted to under 5 cm. In low light conditions, a near-infrared light automatically illuminates the subject. Frame rate, resolution and video compression levels can be set by the user. The system can be remotely controlled using either a smartphone, tablet or laptop via the onboard Wi-Fi. PICT can record up to 72-hr day and night videos at >720p resolution with a 110-Wh power bank (30,000 mAh). Its ultra-portable (<1 kg) waterproof design and modular architecture is practical in diverse field settings. We provide an illustrated technical guide detailing the steps involved in building and operating a PICT and for video post-processing. We successfully field-tested PICT in a Central African rainforest in two contrasting research settings: an insect pollinator survey in the canopy of the African ebony Diospyros crassiflora and the observation of rare pollination events of an epiphytic orchid Cyrtorchis letouzeyi. PICT overcomes many of the limitations commonly associated with CT systems designed to monitor ectotherms. Increased portability and image quality at lower costs allow for large-scale deployment and the acquisition of novel insights into the reproductive biology of plants and their interactions with difficult to observe animals.